Comparison between Islamic and Non-Islamic Banks Ratios to Predict Amman Stock Exchange Banking Index - Ahmad Abdallah Ahmed Alswalmeh; Nuradli Ridzwan Shah Mohd Dali (Asian Scholars Network, 2024)
Non-Indexed Publication